Możliwości zastosowania systemu rachunkowości FADN w rodzinnych gospodarstwach rolnych - Kucharczyk, Małgorzata (Possibilities of Fadn Accounting System Application at Family Farms, 2005)
Agricultural activity currently plays many socio-economic roles. Although agriculture is one of those sectors of economy, whose significance in the process of setting the domestic product value has decreased considerably, one should remember that every farm constitutes an economic entity. Farmers, like other economic entities and other national institutions, need information concerning results of their activity, which would come from an accounting system that has been duly prepared and adjusted to the specific activity of family farms. As a consequence, this paper covers the basic principles of FADN, the farms' individual income measurement system as well as an attempt at analysis of whether it would be possible to apply the FADN procedures at a great number of family farms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 213-221